2013
DOI: 10.1071/ch12546
|View full text |Cite
|
Sign up to set email alerts
|

Production and Regulation of Levels of Amidated Peptide Hormones

Abstract: Peptide hormones with a C-terminal amide regulate numerous physiological processes and are associated with many disease states. Consequently, the key enzymes involved in their production, peptidylglycine α-amidating monooxygenase and carboxypeptidase E, have been studied intensively. This review surveys what is known about the enzymes themselves and their cofactors, as well as their substrates and competitive and mechanism-based inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…We find that inactivated PHM is indistinguishable from untreated enzyme and find no evidence for cinnamate oxidation during the inactivation reaction. The reversible Michael addition of an active site nucleophile to cinnamate could account for our data and may explain the inactivation of PHM by a variety of acrylates 20,30,35 , and the 2- and 3-alkenoates 32 as well as provide an explanation for the lack of PHM-labeling by 3 H-PBA 37 .…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…We find that inactivated PHM is indistinguishable from untreated enzyme and find no evidence for cinnamate oxidation during the inactivation reaction. The reversible Michael addition of an active site nucleophile to cinnamate could account for our data and may explain the inactivation of PHM by a variety of acrylates 20,30,35 , and the 2- and 3-alkenoates 32 as well as provide an explanation for the lack of PHM-labeling by 3 H-PBA 37 .…”
Section: Introductionmentioning
confidence: 58%
“…Like the chemistry proposed for the olefinic inactivation of DβM and P 450 , it has been suggested that olefinic inactivation of PHM results from the formation of a non-epoxide oxidized species, likely an olefin-derived radical 25,33,3538,64 . This hypothesis is reasonable given that inactivation is turnover-dependent and that the PHM-catalyzed hydroxylation reaction likely proceeds through a substrate-based radical 3942 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 'Computational Evaluation of the Sulfonyl Radical as a Universal Leaving Group for RAFT Polymerisation', M. L. Coote et al [11] report an application of free radical chemistry to advance polymer science; M. A. Terzidis and C. Chatgilialoglu [12] use radicals in chemical synthesis in 'Radical Cascade Protocol for the Synthesis of (5 0 S)-and (5 0 R)-5 0 ,8-Cyclo-2 0 -deoxyguanosine Derivatives'; J. A. Murphy and co-workers [13] explore radicals as organic reducing agents in 'A Novel Organic Electron Donor Derived from N-Methylisatin'; and F. Cao and C. J. Easton [14] review the 'Production and Regulation of Levels of Amidated Peptide Hormones', fundamental physiological processes where free radicals are intimately involved.…”
mentioning
confidence: 99%